2002
DOI: 10.1108/14684520210447886
|View full text |Cite
|
Sign up to set email alerts
|

Usage of information resources by computer engineering students: a case study of Nanyang Technological University, Singapore

Abstract: This study investigates the information needs and information seeking behaviour of computer engineering undergraduate students at Nanyang Technological University (NTU), Singapore. The purpose was to investigate the types of information sources used by the students, their preferred information formats, the importance of and reasons for using certain information sources and the use of various electronic information sources. A questionnaire was distributed to 200 randomly selected students and 102 completed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 15 publications
6
45
0
1
Order By: Relevance
“…As per the results, the most demanded facilities were access to computers, followed by the reading area, discussion room, and prayer room, printing and photocopying facilities while self-check machines were also in demand by students. A similar study was done by Majid and Ai (2002) at the Nanyang Technological University, Singapore found that printed materials were the most preferred information format among students. They found that the use of databases and electronic journals was quite low among the Computer Engineering students and recommended promotional campaigns for introducing electronic information sources to the library users.…”
Section: Literature Reviewmentioning
confidence: 86%
“…As per the results, the most demanded facilities were access to computers, followed by the reading area, discussion room, and prayer room, printing and photocopying facilities while self-check machines were also in demand by students. A similar study was done by Majid and Ai (2002) at the Nanyang Technological University, Singapore found that printed materials were the most preferred information format among students. They found that the use of databases and electronic journals was quite low among the Computer Engineering students and recommended promotional campaigns for introducing electronic information sources to the library users.…”
Section: Literature Reviewmentioning
confidence: 86%
“…OCLC (2002), on their white paper on the information seeking behaviour of students reported that 7 out of 10 students used the library's website for some assignments and also the most frequent uses were of full text Journals (67 percent), library catalogue (57 percent), and databases and indexes (51 percent). Majid and Ai (2002), studied the use of information resources by computer engineering students in Singapore and found that the top five information resources in order of preference were books (94 percent), lecturers (84 percent), the Internet (86 percent) and friends (84 percent). They relied heavily on printed sources of information and their use of electronic journals and databases was very low.…”
Section: Information Sources Used In Obtaining Informationmentioning
confidence: 99%
“…Majid and Tan 25 indicated printed materials such as books were the most preferred information format and the use of databases and electronic journals was quite low. Naqvi 26,27 in his studies revealed that the CD-RoM databases such as AGRIS, AGRICOLA, CAB abstract, and agriculture & natural resources; and e-journals were the highly used e-resources by the majority of P.G.…”
Section: Literature Reviewmentioning
confidence: 99%